2019
DOI: 10.29252/jafm.12.05.29583
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Taylor-Couette Flow with Finned Surface Rotation

Abstract: In this study, the Taylor-Couette flow was disturbed by incorporating annular fins over the inner rotating surface. The finned surface had three parameters: height, width, and length between fins. In this work, seven different fin configurations, in which only the fin height varied, were examined and compared using experimental and numerical techniques. We found that annular fins disturbed the flow behavior by reducing the smooth critical Taylor number (Ta=57.18), but more important, we noticed a vortex enlarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Deng et al [26] investigated the structure of the Taylor vortex within the annular gap using horizontal baffles and observed that the number, position, and width of the baffles affected the vortex structure; however, the study did not include axial flow in the TCF. Álvarez et al [27] examined the flow field within the annular gap in the case of an annular ribbon fin structure and noted the appearance of smaller secondary vortices above the fins, as well as an increase in the vortex size with an increase in fin width. It is important to note that any additional contact surface within the TCR annular gap has a significant impact on the Taylor vortex structure.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [26] investigated the structure of the Taylor vortex within the annular gap using horizontal baffles and observed that the number, position, and width of the baffles affected the vortex structure; however, the study did not include axial flow in the TCF. Álvarez et al [27] examined the flow field within the annular gap in the case of an annular ribbon fin structure and noted the appearance of smaller secondary vortices above the fins, as well as an increase in the vortex size with an increase in fin width. It is important to note that any additional contact surface within the TCR annular gap has a significant impact on the Taylor vortex structure.…”
Section: Introductionmentioning
confidence: 99%